Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT. Otscon Safety Indonesia - Muhamad Rizki; Novian Ekawaty (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Employees are a dynamic factor in all operational activities within the company. PT. Otscon Safety Indonesia as a company that applies work discipline to employees to be more productive, comply with regulations and policies in order to provide benefits for the company in achieving company goals optimally in the long term. The research has the aim of knowing the partial and simultaneous influence of employee work discipline, the work environment of existing employees on their performance at PT. Otscon Safety Indonesia is descriptively verifiative. Researchers used as many as 110 employees as respondents as samples taken through saturated sampling technique. The path analysis test resulted in the finding of a partial effect of 47.2% between work discipline on employee performance and 11.9% of the work environment on employee performance. The findings amounted to 59.1% of the simultaneous influence of all variables. Researchers found the influence of other variables outside the model, namely 40.9%. Keyword: Work Discipline, Work Environment, Employee Performance